Inferences about change-points in rehabilitation on the outcome of a knee arthroscopy as a results of patello femoral pain syndrome in sport - Oosthuizen, Jan Jonathan (University of the Free State, 2001)
Rehabilitation is recognized as a critical component in the treatment of sports injuries, and has been the subject of intense research over the past decade. As a result, sound scientific principles have been applied to the realm of rehabilitation data and results. Life in the world as we know it is fast becoming a flustering playground that also affects rehabilitation as such, and especially the cost and time of the rehabilitation programs prescribed. By developing ways to minimize time-consuming efforts and at the same time optimize the efficiency of a rehabilitation program, we will be able to keep up with our constant changing world. As a result of the aforementioned, significant evidence has been found for a Change- Point model using rehabilitation data. A statistical method for analyzing rehabilitation data/sequences containing a Change-Point is therefore proposed. The methods may be extended in many directions. By calculating a patients' Change-Point during his rehabilitation process, one will be able to either take a more aggressive, or a more conservative approach when adjusting the exercise prescription of a patient during the different phases of the rehabilitation process. Evidence suggests that Change-Point analysis may be a completely new direction in rehabilitation as we know it. In order to implement the use of Change-Point analysis on rehabilitation data, one needs to identify an injury(s) along with the treatment used for it. Patello Femoral disorders, especially the Patello Femoral Pain Syndrome (PFPS) is a well-known problem in all age groups. This disorder is a very common complaint amongst the general population. Conservative treatment will always be the first option with regard to rehabilitation of this disorder. If, however, this method fails, the surgeon will opt for a surgical procedure, in this case a procedure known as and arthroscopy. An arthroscopy is a minimally invasive surgical procedure that can be performed for the purpose of diagnosing and the following treatment of problems within the internal structure of joints. Over the past decade, it has become one of the most frequently used procedures for the diagnosis and treatment of knee injuries. In addition, various rehabilitation or treatment modalities are proposed after a patient underwent a knee arthroscopy. One of these modalities is isokinetic exercise. Isokinetic exercise is a popular dimension in the field of resistive exercise and muscle evaluation. It is made possible by an electro-mechanical device that keeps limb motion at a constant, predetermined velocity. Many competitive and recreational athletes perform resistance training as a part of their conditioning program. Resistance training in addition to increasing muscular strength and hypertrophy may also aid in the prevention of injuries. Research indicates that resistance training promotes growth and/or increases in the strength of ligaments, tendons, tendon to hone and ligament to bone junction strength, joint cartilage and the connective tissue sheaths within muscle. Studies involving humans and animal models also demonstrate resistance training can cause increased bone mineral content and therefore may aid in the prevention of skeletal injuries. Change-Point analysis can therefore be of high value to the Biokineticist in helping him/her to evaluate the progress of rehabilitation more successfully. Because of our rapid changing world, it is imperative that new methods of analyzing and interpreting rehabilitation data are developed and created. This will aid in our understanding thereof and it will have a significant effect on the cost, time and outcome of a prescribed, rehabilitation program. Only then, will we as Biokineticists truly fulfill the mission of our profession, which is to improve the quality of life of our fellow human beings.

Rehabilitasie word erken as 'n kritiese komponent in die behandeling van sportbeserings en was die onderwerp van intensiewe navorsing tydens die afgelope dekade. Gevolglik is gegronde wetenskaplike beginsels op die terrein van rehabilitasiedata en -resultate toegepas. Die lewe van vandag word geketunerk deur 'n hoë tempo wat ook rehabilitasie as sodanig, en veral die koste en tyd van die programme, beïnvloed. Deur maniere te ontwikkel wat tydrowende pogings minimaliseer en terselfdertyd die effektiwiteit van programme optimaliseer, word ons in staat gestelom in pas te bly met ons veranderende wêreld. As gevolg van die bogenoemde, is betekenisvolle bewyse gevind vir 'n Draai-punt model waar rehabilitasiedata gebruik kan word. 'J} Statistiese metode waarmee rehabilitasiedata wat 'n Draai-punt bevat geanaliseer word, word in die studie voorgestel. Die metodes kan in verskeierigtings uitgebrei word. Deur 'n pasiënt se Draai-puntte bepaal gedurende die verloop van die rehabilitasie-proses, kan die Biokinetikus duidelik sien of daar 'n meer aggressiewe of meer konserwatiewe benadering gevolg moet word wanneer die oefenprogram-voorskrif aangepas word. Op grond van die studie kom dit voor asof Draai-punt analise 'n splinternuwe dimensie aan tradisionele rehabilitasie kan verleen. Ten einde die gebruik van 'n Draai-punt model geassosieer met rehabilitasiedata, te implementeer, is dit nodig om 'n besering(s) en die betrokke behandeling te identifiseer. Patella Femorale afwykings, en meer spesifiek Patello Femorale Pyn Sindroom (PFPS), is 'n bekende toestand in alle ouderdomsgroepe en ook 'n gereelde klagte onder die algemene populasie. Konserwatiewe behandeling is altyd die eerste opsie tov die rehabilitasie van die probleem. Indien dit nie slaag nie, sal die chirurg 'n operatiewe prosedure oorweeg, in hierdie geval 'n atroskopie. 'n Atroskopie is 'n prosedure wat minimale skending veroorsaak en word uitgevoer om diagnoses te bevestig binne bepaalde gewrigte. Gedurende die afgelope dekade is atroskopie gereeld gebruik vir die diagnose en behandeling van kniebeserings. Verder word daar verskeie rahabilitasie- en behandelings-modaliteite voorgestel nadat 'n pasiënt 'n atroskopie ondergaan het. Een van hierdie modaliteite is isokinetiese oefening. Isokinetiese oefening is 'n populêre dimensie binne die terrein van weerstands-oefening en die evaluasie van spierverhoudings. Hierdie tipe oefening word moontlik gemaak deur 'n elektro-meganiese apparaat wat ledemate teen 'n konstante, voorafbepaalde snelheid laat beweeg. Verskeie kompeterende sowel as rekreasie atlete sluit weerstandsoefeninge by hul kondisionerings-program in. Die beoefening van weerstands-oefeninge ten einde spierkrag en hipertrofie te verhoog, kan ook 'n bydrae lewer ter voorkoming van beserings. Navorsing beaam dat weerstands-oefeninge groei en I of die sterkte van Iigamente, tendons, tendon - been en ligament - been aanhegtings en gewrigs-kraakbeen bevorder. Studies wat op beide mense en diere uitgevoer is, dui aan dat weerstandsoefening tot 'n verhoging in die mineraal-inhoud van bene kan lei. Dit kan help met die voorkoming van skeletale beserings. Samevattend kan gestel word dat Draai-punt analise van onskatbare waarde vir die Biokinetikus kan wees aangesien dit hom/haar kan help om die vordering van die rehabilitasie-proses meer suksesvol te meet. Vanweë ons snel veranderende wêreld, is dit noodsaaklik dat nuwe metodes geskep en ontwikkel word wat ons in staat stelom rehabilitasiedata te analiseer en te interpreteer. Hierdie metodes sal 'n betekenisvolle invloed hê op die uitkoms, koste en tyd van die voorgeskrewe rehabilitasieprogram. Deur die lewenskwaliteit van medemense te vetbeter, sal Biokinetici eers werklik die opdrag van hul professie volbring.
Dissertation (M.A. (Human Movement Studies))--University of the Free State, 2001
Keywords: Change-points; Patello femoral pain syndrome; Arthroscopy; Isokinetic test design; Bayesian statistics; Knee -- Surgery; Isokinetic exercise